Morphological, morphometric and radiographic studies on the skull of lesser mole-rats (Nannospalax leucodon) - Amina Rizvanovic; Nedzad Hadziomerovic; Pamela Bejdic; Jasminko Mulaomerovic (Macedonian Veterinary Review, 2022)
Lesser mole-rats (Nannospalax leucodon) are members of the Rodentia order’s Spalacidae family, and they are found in Northeastern Africa, the Balkans, Southeastern Europe, Central Asia, the Middle East, and Caucasia. The shape of the skull has a significant impact on the phenotypic appearance of animal heads, and although many domestic species have been studied, there is a lack of evidence on the macro-anatomical characteristics of the skeletal system in mole-rats. The current research was focused on the morphological, morphometric, and radiographic properties of lesser mole-rats skull in Bosnia and Herzegovina. The research was conducted on five lesser mole-rats from Bjelasnica Mountain, Bosnia and Herzegovina. We compared the results of the previously published studies, and we found a lot of similarities between Nannospalax leucodon in Bosnia and Herzegovina and Nannospalax ehrenbergi in North Iraq, as well as the Nannospalax nehringi from Eastern Anatolia.